Point-of-care testing system for digital single cell detection of MRSA directly from nasal swabs. Issue 14 (22nd June 2020) - Schulz, Martin; Calabrese, Silvia; Hausladen, Florian; Wurm, Holger; Drossart, Dominik; Stock, Karl; Sobieraj, Anna M.; Eichenseher, Fritz; Loessner, Martin J.; Schmelcher, Mathias; Gerhardts, Anja; Goetz, Ulrike; et al.
Abstract : Automated point-of-care testing system for rapid single cell detection of MRSA directly from nasal swab samples. Abstract : We present an automated point-of-care testing (POCT) system for rapid detection of species- and resistance markers in methicillin-resistant Staphylococcus aureus (MRSA) at the level of single cells, directly from nasal swab samples. Our novel system allows clear differentiation between MRSA, methicillin-sensitive S. aureus (MSSA) and methicillin-resistant coagulase-negative staphylococci (MR-CoNS), which is not the case for currently used real-time quantitative PCR based systems. On top, the novel approach outcompetes the culture-based methods in terms of its short time-to-result (1 h vs. up to 60 h) and reduces manual labor. The walk-away test is fully automated on the centrifugal microfluidic LabDisk platform. The LabDisk cartridge comprises the unit operations swab-uptake, reagent pre-storage, distribution of the sample into 20 000 droplets, specific enzymatic lysis of Staphylococcus spp. and recombinase polymerase amplification (RPA) of species (vicK) – and resistance (mecA) -markers. LabDisk actuation, incubation and multi-channel fluorescence detection is demonstrated with a clinical isolate and spiked nasal swab samples down to a limit of detection (LOD) of 3 ± 0.3 CFU μl −1 for MRSA. The novel approach of the digital single cell detection is suggested to improve hospital admission screening, timely decision making, and goal-oriented antibiotic therapy. The implementation of a higher degree of multiplexing is required to translate the results into clinical practice.